Role of CD135/CD117 on Prognosis and Overall Survival of Acute Myeloid Leukemia - Raeisi, Mortaza (Asian Pac J Cancer Prev, 2019)
BACKGROUND: The key proliferative RTKs for AML include c-KIT receptor (CD117) and FLT-3 receptor (CD135). The aim of this study was to evaluate the CD135 and CD117 expression, co-expression of CD135 and CD117 (CD135+CD117), and the association of that co-expression with Event Free Survival (DFS) and Overall Survival (OS) rates. MATERIAL AND METHODS: We analyzed CD117 and CD135 expression on AML blasts by flow cytometry and its association with Event Free Survival (DFS) and Overall Survival (OS) in 66 AML treated on Hematology-Oncology Research Center, Iran, Tabriz. RESULTS: The overall OS and EFS were 50% and 80.3% respectively during our study. Cox-regression analysis revealed that a poor EFS was significantly associated a low CD135 (HR 0.34, 95% CI 0.13–0.88, P = 0.02). CONCLUSION: This is the first study from Iran to show that the expressions of CD135, CD117 is easily measurable by routine diagnostic flow-cytometry, and CD135+117 were not significantly associated with CR, EFS, or OS .